Influence of Nb2O5 doping to energy-storage properties of (Na0.5Bi0.5)0.705Ba0.045Sr0.25TiO3 lead-free ferroelectric ceramics. Issue 1 (1st April 2021) - Wu, Ruifang; Liang, Linlin; Duan, Ruijie; Zhao, Jinghao; Li, Zekai; Bian, Gang; Wang, Jing
Abstract: The powder samples of (Na0.5 Bi0.5 )0.705 Ba0.045 Sr0.25 TiO3 - x Nb2 O5 (NBBSNT) were synthesized by a wet solid-phase method. The effects of Nb-doping on morphology, ferroelectric and dielectric properties of samples were investigated. Typical surface morphologies by scanning electron microscopy for the NBTBZN ceramics showed grain size decreasing. Dielectric measurements revealed that the depolarization temperature and Curie temperature shifted to lower temperature. With the increase of Nb content, the ferroelectric hysteresis loops became much slimmer, coupled with the reduction in remnant polarization and coercive field. Energy storage density of 0.855 J/cm 3 and the energy storage efficiency of 74.26% were obtained for NBBSNT with x = 0.09.